Inflation and Its Contribution to Economic Stability in Indonesia; The Islamic Economic Perspective - Widya, Fira Arista (Department of Islamic Accounting, The Faculty of Islamic Economics and Business, State Islamic Institute of Kediri [IAIN Kediri, 2023)
Inflation has decreased compared to times that have been exceeded, however, its journey has slowed down. The development of GDP achievements also accompanies this. This paper aims to analyze the slowing down in inflation decline and its impact on economic stability. This paper is reviewed with a qualitative approach and research type of literature study . This paper shows that reducing inflation is one of the efforts to maintain the stability of a country's economy and economic stability is an important factor in maintaining the sustainability of a country's economy.